Estudio de la distribución de anfibios en el páramo del Parque Nacional Podocarpus, frente a posibles escenarios de cambio climático - Guzmán Sarango, Edison Geovanny (2015)
This research is modeling the distribution of habitat for four species of frogs: Pristimantis myersi, Pristimantis colodactylus, Pristimantis orcesi and Pristimantis percultus; all present in the Moorland of the Podocarpus National Park, specifically in the area of Cajanuma. The modeling was performed from a record of presences of species, climate variables as mean annual temperature and mean annual precipitation (Bio1 and Bio12) and a topographic variable corresponding to the altitude (MDE). Using software that employs an algorithm of entropy (MaxEnt), the current potential distribution was obtained, and potential future distribution model under which the RCP 6.0 and RCP 8.5 scenarios for the year 2050. Afterwards with the software ArcGis vectorization of the location was conducted, and proceeded to generate the final maps. The information required to generate the models was obtained from the following sources: registers the presence of the species were obtained from the database generated by Salinas and Veintimilla (2010), climatic variables were obtained from the database WorldClim and were 1 km2 resolution, and topographic variable was obtained from the MICCAMBIO database project. The results showed that for the year 2050 all species will lose some of its actual area of distribution, given that under the RCP 8.5 scenario that more area will be lost under the RCP 6.0 scenario, however the difference is not very marked, except Pristimantis percultus that under the RCP 6.0 scenario loses 19.4% of actual area and under the RCP 8.5 scenario lost 30.7%.